2015
DOI: 10.1007/s40675-015-0011-2
|View full text |Cite
|
Sign up to set email alerts
|

Borderline Personality Pathology, Polysomnography, and Self-Reported Sleep Problems: A Review

Abstract: There is a growing body of research that links borderline personality pathology to sleep disturbance through polysomnography (PSG) and self-report studies. Twelve PSG studies are reviewed that found sleep differences in recordings of sleep parameters such as sleep continuity, non-REM sleep, and REM sleep in borderline personality disorder (BPD) patients compared to controls. Further, since the turn of the century, self-report methodology has been increasingly utilized to investigate this relationship, and find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 53 publications
3
17
3
Order By: Relevance
“…Also in contrast to conclusions from previous reviews (Oltmanns & Oltmanns, 2015a), we found that patients with BPD experienced significantly shorter REM latency than HCs. This finding was robust across several sub-groups, including depression status, sample type, and sex.…”
Section: Do Individuals With Bpd Significantly Differ From Healthy Ancontrasting
confidence: 99%
See 4 more Smart Citations
“…Also in contrast to conclusions from previous reviews (Oltmanns & Oltmanns, 2015a), we found that patients with BPD experienced significantly shorter REM latency than HCs. This finding was robust across several sub-groups, including depression status, sample type, and sex.…”
Section: Do Individuals With Bpd Significantly Differ From Healthy Ancontrasting
confidence: 99%
“…They did, however, demonstrate significantly less SWS. This result contrasts with previous reviews, which did not identify a difference in SWS between BPD and HCs (Oltmanns & Oltmanns, 2015a), or suggested a potential increase in SWS in BPD (Simor & Horváth, 2013). Discrepant conclusions across reviews are likely partly due to a lack of power in individual studies (i.e., null findings, which when combined in meta-analysis reveal significant associations).…”
Section: Do Individuals With Bpd Significantly Differ From Healthy Ancontrasting
confidence: 89%
See 3 more Smart Citations